Acute and Sub-acute Safety Studies of a Herbal Formulation for Urolithiasis in Laboratory Animals - Patankar, Suresh; Mujumdar, Arvind (Novel Aspects on Pharmaceutical Research Vol. 1, 2023)
This study reported a preclinical acuteand sub-acute safety profiles of Hermed plus (HP) were investigated in laboratory animals. This is a very effective formulation developed in house. We have systematically studied the effec in Laboratory Animals for its behavioral changes or mortality if any, hematological parameters and found no hepato or renal toxicity associated with the sub-chronic dermal exposure of investigational product in the animals. The study was conducted in female Swiss albino mice using OECD guidelines Number 423. HP was derived from Crataeva nurvala Buch - Ham (Varun) bark, Musa paradisiaca Linn (Kadali / Banana) stem and roots, Achyranthes aspera Linn (Aghada) whole plant and Hordeum vulgare Linn (Yav) seeds. Above materials were converted into Varun bhavi, kadali bhavit, kshars of Kadali, Aghada and Yav respectively and were mixed in certain proportions in GMP certified manufacturing facility to formulate HP capsules form.Acute and sub-acute safety profiles of HP was studied by OECD guidelines Number 423 and FDA guidelines in Swiss albino mice and Wistar rats respectively. For the acute study, HP was administered orally in a single dose of 2000mg/kg and for sub-acute study HP was administered orally using S90,180 and 450mg/kg doses for 90days. In the present sub-acute study at termination the weights of vital organs like adrenals, heart, kidneys, liver, spleen, lungs, testis/ ovaries were determined and were converted into relative % organ weight and these were compared with control rats.In comparison to control animals, the subacute oral therapy with 90 mg/kg, 180 mg/kg, and 450 mg/kg of HP for 90 days to several groups of rats revealed no mortality, no behavioural alterations, and no changes in blood profile, biochemistry parameters, or profiles of essential organs. Hence, the NOAEL for HP in male and female Wistar rats was determined to be > 450 mg/kg when administered orally for 90 days.